PENGARUH PRICE DISCOUNT DAN SALES PROMOTION TERHADAP LOYALITAS PELANGGAN PADA SATRIA JAYA MOTOR - Rijal Efendi; Sri Wahyuni Mega; Diana Ambarwati (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to determine the influence of price discounts and sales promotions on customer loyalty. The research method used is a quantitative method with a descriptive approach. Data collection in this research was carried out by distributing questionnaires to Satria Jaya Motor customers and calculated using the SPSS Version 25 application. The population in the study was 253 customers with a sample of 155 customers taken in March-April 2023. Data analysis techniques used included Test Validity, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, t Test, F Test, and R2 Coefficient of Determination Test. In the Validity Test, it is known that all question items (X1, X2, and Y) have a significance value of 0.000 < 0.05 so that each variable is declared valid. Then in the Reliability Test each variable was declared reliable because it had a Cronbach's Aplha value > 0.60. Then in the t test it is known that the price discount (X1) and sales promotion (X2) variables have a significance value of 0.000 <0.05 so that these two variables partially have a significant effect on customer loyalty (Y). Then the F test shows that the significance value is 0.000 <0.05, which shows that price discounts and sales promotions have a simultaneous effect on customer loyalty to Satria Jaya Motor.